2014 consensus statement on improving pelvic floor muscle training adherence: International Continence Society 2011 State‐of‐the‐Science Seminar. Issue 7 (21st May 2015) - Dumoulin, Chantale; Hay‐Smith, Jean; Frawley, Helena; McClurg, Doreen; Alewijnse, Dianne; Bo, Kari; Burgio, Kathryn; Chen, Shu‐Yueh; Chiarelli, Pauline; Dean, Sarah; Hagen, Suzanne; Herbert, Julia; et al.
<x xml:space="preserve">Abstract</x> Aims To summarize the findings and "expert‐panel" consensus of the State‐of‐the‐Science Seminar on pelvic floor muscle training (PFMT) adherence held prior to the 41st International Continence Society scientific meeting, Glasgow, 2011. Methods Summaries of research and theory about PFMT adherence (based on a comprehensive literature search) were presented by subject experts at the 2011 Seminar to generate discussion and guidance for clinical practice and future research. Supplemental research, post‐seminar, resulted in, three review papers summarizing: (1) relevant behavioral theories, (2) adherence measurement, determinants and effectiveness of PFMT adherence interventions, and (3) patients' PFMT experiences. A fourth, reported findings from an online survey of health professionals and the public. Results Few high‐quality studies were found. Paper I summarizes 12 behavioral frameworks relevant to theoretical development of PFMT adherence interventions and strategies. Findings in Paper II suggest both PFMT self‐efficacy and intention‐to‐adhere predict PFMT adherence. Paper III identified six potential adherence modifiers worthy of further investigation. Paper IV found patient‐related factors were the biggest adherence barrier to PFMT adherence. Conclusion Given the lack of high‐quality studies, the conclusions were informed by expert opinion. Adherence is central to short‐ and longer‐term PFMT effect. More attention and explicit reporting is needed regarding: (1) applying health behavior theory in PFMT program planning; (2) identifying adherence determinants; (3) developing and implementing interventions targeting known adherence determinants; (4) using patient‐centred approaches to evaluating adherence barriers and facilitators; (5) measuring adherence, including refining and testing instruments; and (6) testing the association between adherence and PFMT outcome. Neurourol. Urodynam. 34:???–???, 2015. © 2015 Wiley Periodicals, Inc.